Conviction - Gilbert, Kelly Loy. (2015)
"A small-town boy questions everything he holds to be true when his father is accused of murder"--
Keywords: Fathers and sons -- Juvenile fiction; Faith -- Juvenile fiction; Trials (Murder) -- Juvenile fiction; Fathers and sons -- Fiction; Faith -- Fiction; Trials (Murder) -- Fiction; Young adult fiction